PENGARUH DEWAN DIREKSI, KOMITE AUDIT, DAN KEBERAGAMAN GENDER TERHADAP KINERJA KEUANGAN (STUDI KASUS: PERBANKAN SYARIAH DI INDONESIA DAN MALAYSIA) - Astuti, Wiji; Septianingrum, Vina; Mirojiah, Syahrotul; Nahriah, Sitatun; Nofryanti, Nofryanti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This research aims to examine the influence of board of directors size, audit committee size, and gender diversity on financial performance in Islamic banking in Indonesia and Malaysia. The approach used in this research is explanatory quantitative. The sample selection technique uses a purposive sampling technique by applying three main criteria. Based on the required criteria, there are 23 Islamic banks from Indonesia and Malaysia that meet the sample, and observations were made over a 3-year period, namely 2021 to 2023. The research data was processed using the Eviews 13 software application. The results of this research show that simultaneously or in the F test, the variables size of the board of directors, size of the audit committee, and gender diversity have a significant effect on financial performance in Islamic banking in Indonesia and Malaysia. However, the results of the partial test, or t-test, show that the size of the board of directors, the size of the audit committee, and gender diversity do not have a significant effect on the financial performance of Islamic banking in Indonesia and Malaysia.